Comparative metabolic profiling of Haberlea rhodopensis, Thellungiella halophyla, and Arabidopsis thaliana exposed to low temperature - Benina, Maria; Obata, Toshihiro; Mehterov, Nikolay; Ivanov, Ivan; Petrov, Veselin; Toneva, Valentina; Fernie, Alisdair; Gechev, Tsanko S. (Frontiers in Plant Science, 2013)
Haberlea rhodopensis is a resurrection species with extreme resistance to drought stress and desiccation but also with ability to withstand low temperatures and freezing stress. In order to identify biochemical strategies which contribute to Haberlea’s remarkable stress tolerance, the metabolic reconfiguration of H. rhodopensis during low temperature (4°C) and subsequent return to optimal temperatures was investigated and compared with that of the stress tolerant Thellungiella halophyla and the stress sensitive A. thaliana. The effect of the low temperature treatment in the three species was confirmed by gene expression of low-temperature- and dehydration-inducible genes. Metabolic analysis by GC-MS revealed intrinsic differences in the metabolite levels of the three species even at 21°C. H. rhodopensis had significantly more raffinose, melibiose, trehalose, myo-inositol, sorbitol, and galactinol than the other two species. A. thaliana had the highest levels of putrescine and fumarate, while T. halophila had much higher levels of several amino acids, including alanine, asparagine, beta-alanine, histidine, isoleucine, phenylalanine, serine, threonine, and valine. In addition, the three species responded differently to the low temperature treatment and the subsequent recovery, especially with regard to the sugar metabolism. Chilling induced accumulation of maltose in Haberlea and raffinose in A. thaliana, but raffinose levels in low temperature exposed Arabidopsis were still much lower than these in unstressed Haberlea. While all species accumulated sucrose during chilling, that accumulation was transient in Haberlea and Arabidopsis but sustained in T. halophila after the return to optimal temperature. In T. halophila, the levels of proline and hydroxyproline drastically increased upon recovery. Collectively, these results show inherent. differences in the metabolomes under the ambient temperature and the strategies to respond to low temperature in the three species.